2024
DOI: 10.1101/2024.02.06.579159
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping glycoprotein structure reveals defining events in the evolution of theFlaviviridae

Jonathon C.O. Mifsud,
Spyros Lytras,
Michael R. Oliver
et al.

Abstract: SummaryViral glycoproteins drive membrane fusion in enveloped viruses and determine host range, tissue tropism and pathogenesis. Despite their importance, there is a fragmentary understanding of glycoproteins within theFlaviviridae; for many species the glycoproteins have not yet been identified, for others, such as the hepaciviruses, the molecular mechanisms of membrane fusion remain uncharacterised. Here, we combine comprehensive phylogenetic analyses with systematic protein structure prediction to survey gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 102 publications
1
6
0
Order By: Relevance
“…Despite the large degree of sequence divergence between viruses of fish and higher vertebrates, there are often striking similarities in the structure and function of viral structural proteins. Such similarities have been observed among the Hepadnaviridae , Orthomyxoviridae , Paramyxoviridae , and Flaviviridae ( 4 , 136 138 ). For example, the neuraminidase surface glycoprotein of Wuhan spiny eel influenza virus, that phylogenetically clusters with influenza viruses ( Fig.…”
Section: Diversity and Evolution Of Fish Virusessupporting
confidence: 56%
“…Despite the large degree of sequence divergence between viruses of fish and higher vertebrates, there are often striking similarities in the structure and function of viral structural proteins. Such similarities have been observed among the Hepadnaviridae , Orthomyxoviridae , Paramyxoviridae , and Flaviviridae ( 4 , 136 138 ). For example, the neuraminidase surface glycoprotein of Wuhan spiny eel influenza virus, that phylogenetically clusters with influenza viruses ( Fig.…”
Section: Diversity and Evolution Of Fish Virusessupporting
confidence: 56%
“…( D ) Homology between sequence block 16 (with putative glycoprotein region) and Chikungunya virus (CHIKV) E1 structure (PDB: 6NK6), the top hit returned by Foldseek, displayed as in ( C ). ( E ) RdRp maximum likelihood phylogeny for the Flaviviridae as described by Mifsud et al ( 27 ). The tree is labeled and colored to indicate major viral genera and groups.…”
Section: Resultsmentioning
confidence: 99%
“…However, viral proteins are underrepresented in fold-based homology search servers such as Foldseek. To address this, we previously generated a protein foldome for the Flaviviridae composed of predicted structures for >450 viral species, all processed using the 300-residue sequence block strategy described above ( 27 ). We queried this database for similarity to the RdRp and glycoprotein folds identified in the sponge flavi-like virus using Foldseek ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As structural data is becoming more readily available, the wealth of information it provides should be incorporated into our understanding of the functional conservation of viral proteins throughout time. Indeed, recent studies have shown that structure-based phylogenetic analyses can outperform sequence-based phylogenetic analyses (9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…The conserved RdRp domain has been the focal point for many evolutionary analyses (7,8). While traditional phylogenomics utilizes metagenomics data, sequence alignments, and comparison metrics, the ever-expanding wealth of structural information provides a potential avenue for the refinement of important branching points (9)(10)(11)(12)(13)(14)(15)(16)(17). In particular, structural comparisons of RdRp domains of different virus families have illustrated surprising similarity amongst Orthomyxoviridae (with negative-sense ssRNA), Flaviviridae (with positive-sense ssRNA) and Cystoviridea (with dsRNA), suggesting NSVs originated from dsRNA viruses which in turn evolved from positive-sense ssRNA viruses (14).…”
Section: Introductionmentioning
confidence: 99%